Microstructure and Mechanical Properties of Ti Cold-Spray Splats Determined by Electron Channeling Contrast Imaging and Nanoindentation Mapping. (5th March 2015) - Goldbaum, Dina; Chromik, Richard R.; Brodusch, Nicolas; Gauvin, Raynald
Abstract: Cold spray is a thermo-mechanical process where the velocity of the sprayed particles affects the deformation, bonding, and mechanical properties of the deposited material, in the form of splats or coatings. At high strain rates, the impact stresses are converted into heat, a phenomenon known as adiabatic shear, which leads to grain re-crystallization. Grain re-crystallization and growth are shown to have a direct impact on the mechanical properties of the cold-sprayed material. The present study ties the microstructural features within the cold-sprayed Ti splats and the substrate to the bonding mechanism and mechanical properties. High-resolution electron channeling contrast imaging, electron backscatter diffraction mapping, and nanoindentation were used to correlate the microstructure to the mechanical properties distribution within the titanium cold-spray splats. The formation of nanograins was observed at the titanium splat/substrate interface and contributed to metallurgical bonding. An increase in grain re-crystallization within the splat and substrate materials was observed with pre-heating of the substrate. In the substrate material, the predominant mechanism of deformation was twinning. A good relationship was found between the hardness and distribution of the twins within the substrate and the size distribution of the re-crystallized grains within the splats.